2020
DOI: 10.3390/molecules25133032
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Characteristics of an Aroma-Blending Mixture by Investigating the Network of Shared Odors and the Molecular Features of Their Related Odorants

Abstract: The perception of aroma mixtures is based on interactions beginning at the peripheral olfactory system, but the process remains poorly understood. The perception of a mixture of ethyl isobutyrate (Et-iB, strawberry-like odor) and ethyl maltol (Et-M, caramel-like odor) was investigated previously in both human and animal studies. In those studies, the binary mixture of Et-iB and Et-M was found to be configurally processed. In humans, the mixture was judged as more typical of a pineapple odor, similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…[2,12] There are certain relationships between molecular structure and scent that are well-documented. [2,8,[13][14][15] For instance, it is known that esters tend to have a fruity and floral scent while thiols often are described as having a rotten or alliaceous scent. [8,14] Even though both tert-amyl acetate and n-amyl acetate have the ester functional group and are very similar in structure, tert-amyl acetate has a camphoraceous scent while n-amyl acetate has a fruity scent.…”
Section: Introductionmentioning
confidence: 99%
“…[2,12] There are certain relationships between molecular structure and scent that are well-documented. [2,8,[13][14][15] For instance, it is known that esters tend to have a fruity and floral scent while thiols often are described as having a rotten or alliaceous scent. [8,14] Even though both tert-amyl acetate and n-amyl acetate have the ester functional group and are very similar in structure, tert-amyl acetate has a camphoraceous scent while n-amyl acetate has a fruity scent.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the overall aroma of a mixture of many compounds is not just the sum of the intensity of their individual aroma descriptors [ 5 , 46 ]. The sense of aroma is influenced by olfactory coding (still poorly understood) and olfactory perception, the understanding of which has been greatly improved in recent years [ 47 ]. It has been shown that, for as little as four compounds that create the aroma mixture, a loss of their individual aroma notes can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the top ten analytes were shared across all three single-hopped beers, although they varied in abundance (β-myrcene, 2-methylbutyl 2-methylpropoanoate, ethyl octanoate, ethyl trans-4-decenoate, ethyl decanoate, β-caryophyllene, and α-humulene). According to published odor descriptions of these analytes, the ethyl esters create a fruity, pineapple, pear, and brandy aroma while the monoterpenes and sesquiterpenes add woody, spicy, herbal notes at specific perception thresholds [17][18][19][20]. The aroma of 2-methylbutyl 2-methyl propanoate has been described as 'earthy' [19].…”
Section: Comparison Of Hop Varieties (Azacca Idaho-7 and Sultana)mentioning
confidence: 99%
“…and sesquiterpenes add woody, spicy, herbal notes at specific perception thresholds [17][18][19][20]. The aroma of 2-methylbutyl 2-methyl propanoate has been described as 'earthy' [19].…”
Section: Comparison Of Hop Varieties (Azacca Idaho-7 and Sultana)mentioning
confidence: 99%